ANALISIS KORELASI SOMERS’D PADA DATA TINGKAT KENYAMANAN SISWA-SISWI SMP PLUS MELATI SAMARINDA - Kriesniati, Prastika; Yuniarti, Desi; Nohe, Darnah A. (PATTIMURA UNIVERSITY, 2013)
Somers'd correlation is a analysis of correlate is used for data with ordinal scale and formed in a contingency table. Somers'd correlation can be used for symmetric and asymmetric relationships. In this case, will be explained about Somers’d asymmetric correlation. Somers'd dYX correlation for asymmetrical association applied to data from questionnaires about their comfortable level of Students live in dorms of Melati formed into 2 contingency table, the contingency table for boarding facilities with the comfortable level of students and the quality of the food with the comfortable level of students. Based on the analysis of correlation Somers'd dYX, it can be seen that there is relationship between boarding facility with comfortable level of students and quality of food with comfortable level of students, and then correlation coefficient from 2 contingency table is 0,330 and 0,345 respectively